1982
DOI: 10.1111/j.1559-1816.1982.tb00872.x
|View full text |Cite
|
Sign up to set email alerts
|

The Portrayal of Aggression on North American Television1

Abstract: The past decade has seen an accumulation of evidence that TV viewing influences beliefs about social reality, particularly in areas related to violence. Detailed content analyses of the portrayal of aggression on North American television were conducted in an attempt to document some of the symbolic messages in television content and the extent to which those messages vary according to program category. The TV sample analyzed consisted of 109 programs (81 hours) chosen on the basis of audience viewing figures;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
2

Year Published

1988
1988
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 17 publications
1
27
0
2
Order By: Relevance
“…As in the study by Williams et al [1982] the analysis also included psychological forms of aggression, because verbal abuse and control by threat is prevalent in TV stories. Aggression on TV was defined as any action causing or attempting to cause physical or psychological harm to onself, another person, animal, or inanimate object, intentionally or accidentally.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As in the study by Williams et al [1982] the analysis also included psychological forms of aggression, because verbal abuse and control by threat is prevalent in TV stories. Aggression on TV was defined as any action causing or attempting to cause physical or psychological harm to onself, another person, animal, or inanimate object, intentionally or accidentally.…”
Section: Methodsmentioning
confidence: 99%
“…The term "aggression" is used here as in the study by Williams et al [1982]. Some other researchers, Gerbner et al [1979, 19801 andCumberbatch et al [1987], have used mostly the term "violence," the definition of which emphasizes physical aggression.…”
Section: Methodsmentioning
confidence: 99%
“…Many media effects studies focus on the impact of violence and physically aggressive behavior on viewers. Based on the work of previous scholars who expanded their view of antisocial behavior to include verbal forms of violence (Potter & Ware, 1987;Williams, Zabrack, & Joy, 1982) as well as theft and deceit (Greenberg, Edison, Korzenny, Fernandez-Collado, & Atkin, as cited in Potter et al, 1997), Potter et al (1997) defined antisocial behavior as ''any action that serves to diminish something in a physical, psychological, social, or emotional manner'' (p. 77). Based on these previous studies, Potter et al also developed a scheme to content analyze the antisocial behavior depicted in prime-time reality-based television programs that included six factors: serious assault, minor assault, theft, verbal aggression, deceit, and accidents.…”
Section: Antisocial Behavior On Survivormentioning
confidence: 98%
“…In counterpoint to this perspective, content analyses have consistently found that the rate of violence on cartoons is much higher than in other types of programs (e.g., see Gerbner, Gross, Morgan, & Signorielli, 1980;Greenberg, Edison, Korzenny, Fernandez-Collado, & Atkin, 1980;National Television Violence Study, 1996), and it is fairly high across all types of comedy programs (Barcus, 1978;Cumberbatch, Lee, Hardy, & Jones, 1987;Gerbner et al, 1980;Lichter & Lichter, 1983;Mustonen & Pulklinen, 1993;Williams, Zabrack, & Joy, 1982).…”
Section: Introductionmentioning
confidence: 95%